The Synergistic Impact of Artificial Intelligence on DevOps: A Comprehensive Review - Kowshik Sakinala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative impact of Artificial Intelligence (AI) on DevOps practices, examining how AI-driven innovations are revolutionizing software development and operations. It delves into key areas where AI is making significant contributions, including AI-assisted development, predictive pipeline management, and enhanced security measures. The article discusses how AI-powered tools are augmenting human capabilities in coding, automating workflow management, and providing real-time threat detection and remediation. Through case studies in the financial services and e-commerce sectors, the article illustrates the real-world applications and benefits of AI integration in DevOps. It also addresses the challenges and limitations of AI adoption, such as potential biases and the need for continuous learning. The discussion concludes with an outlook on prospects, highlighting the evolving landscape of human-AI collaboration in DevOps and the potential for AI to take on more complex roles in software development processes. Overall, this comprehensive article review underscores the pivotal role of AI in driving efficiency, reliability, and innovation in modern software delivery practices, while emphasizing the continued importance of human expertise in guiding these technological advancements.